Further Excavations (1965) at the Middle Acheulian Occupation Site at Latamne, Northern Syria: General Results, Definitions and Interpretations - Clark, J. Desmond
Introduction — The 1965 Excavations – Description of the 1965 Artifacts; ersch. 1967.